Framing of nutrition policy issues in the Australian news media, 2008‐2018 - Kirstin Wise; Katherine Cullerton (Elsevier, 2021)
Abstract Objective: Media framing of nutrition policy issues has been said to play a critical role in influencing public and political support for these issues. We examined the coverage of nutrition policy issues in the Australian news media to determine the key frames and expert sources used by the media. Methods: News articles published in Australia between 2008 and 2018 were retrieved from key media databases. Content analysis was used to identify nutrition policy issues reported and expert sources used. Frames were identified using a theoretical framework. Results: Seven nutrition policy categories were identified. Expert sources included representatives from public health, food industry and politicians. Six dominant frames were identified: government responsibility, industry responsibility, societal frame, individual responsibility, parental responsibility and nanny state frame. Nutrition experts tended to use thematic frames while government and food industry sources used episodic frames to deflect responsibility onto individuals. Conclusions: Despite high media representation of thematic frames and government responsibility in addressing nutrition policy issues, limited regulatory policy action has occurred in Australia. Implications for public health: Further research is needed to better understand different frames and their effectiveness in influencing public and political opinion. Greater coherence amongst health advocates would be beneficial to ensure a collective, recognised voice on issues.